Identification and analysis of industry initiatives in improving remanufacturing in India. (2016) - Sharma, Vaishali; Garg, S.K.; Sharma, P.B.
Remanufacturing is an important manufacturing activity for any economy as it helps to provide processing equipment and products at a lower cost and also helps to reduce environmental degradation and green house gasses. In spite of its economic, environmental and social importance it is not getting the due focus and thus there is a need to take initiatives by different domestic players in India. In this paper, the various initiatives which can be taken by different industries are identified and by using the approach of principal component analysis, they are classified into four factors for better understanding and implementation. The exercise resulted in the extraction of four factors.